MODEL POLA ASUH ORANGTUA TERHADAP PERILAKU ANAK - Sari, Ilda Permata; Elvawati, Elvawati; Yatim, Yenita (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research is motivated by working parents, both parents work in the informal sector. Working parents are busy outside the home which can lead to a lack of communication between parents and children so that parents do not know about their child"™s development. The purpose of this study is to describe the parenting model of working parents on children"™s behavior. The approach used in this study is a descriptive qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation studies. The unit of analysis in this study is the family. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions.